The Influence of Compensation Components On Organizational Citizenship Behavior (OCB) Employees At Mahalona Health Center Towuti District East Luwu - Sahriani, Sahriani; M. Hidayat; Muhammad Akib (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to analyze the effect of compensation components on Organizational Citizenship Behavior at the Mahalona Health Center, Towuti District, East Luwu Regency. The population in this study were 83 employees at the Mahalona Health Center. And this study used a purposive sample sampling technique with certain considerations. Then the sample used was 45 people using the Slovin formula. This research data was obtained from a questionnaire (primary data). The results of research from data processed using SPSS Version 25 statistical calculations, based on the results of SPSS output partially the results showed that partially the variables of financial compensation and non-financial compensation Organizational Citizenship Behavior. Other results found that the variables of financial compensation and nonfinancial compensation had no significant effect on Organizational Citizenship Behavior with a significant value for financial compensation of 0.001 < 0.05 and a significant value for non financial compensation of 0,000 < 0.05. Financial compensation and non financial compensation do not have a positive and significant effect on Organizational Citizenship Behavior.